2020
DOI: 10.1177/1352458520951382
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training reduces neutrophil-to-lymphocyte ratio in persons with multiple sclerosis during inpatient rehabilitation

Abstract: In persons with multiple sclerosis (PwMS), the neutrophil-to-lymphocyte ratio (NLR) is associated with disability status, symptomatology and disease activity. High-intensity interval training (HIIT) improves many symptoms in PwMS and may positively influence disease progression. Here, we present results from a randomized controlled trial during inpatient rehabilitation on immediate (single bout) and training (3-week intervention) effects of HIIT versus moderate continuous training on NLR and related cellular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 10 publications
2
27
1
1
Order By: Relevance
“…In response to acute exercise 9 of 11 studies revealed an increase of NLR (see Table 2), suggesting good suitability for depiction of exercise-induced inflammation. Additionally, Joisten et al (2020) demonstrated an intensity-dependent increase of NLR in response to acute exercise with significantly higher NLR values Nieman et al 1995). In contrast, chronic exercise interventions seem to show conflicting results at first sight.…”
Section: Current State Of Knowledge-nlr Plr and Sii In Exercise Physmentioning
confidence: 95%
“…In response to acute exercise 9 of 11 studies revealed an increase of NLR (see Table 2), suggesting good suitability for depiction of exercise-induced inflammation. Additionally, Joisten et al (2020) demonstrated an intensity-dependent increase of NLR in response to acute exercise with significantly higher NLR values Nieman et al 1995). In contrast, chronic exercise interventions seem to show conflicting results at first sight.…”
Section: Current State Of Knowledge-nlr Plr and Sii In Exercise Physmentioning
confidence: 95%
“…Then, stroke is associated with a strong neuroinflammation that affects neuroplasticity processes within the core of lesion, the penumbra and the remote areas such as the spinal cord [91][92][93][94]. HIIT might be suitable to reduce pro-inflammatory cytokines in parallel with an activation of microglia (M2 phenotype) in rodents with cerebral ischemia as well as the neurotrophil-to-lymphocyte ratio in patients with multiple sclerosis [38,95].…”
Section: How Can Hiit Promote Neuroplasticity and Cognitive Benefits mentioning
confidence: 99%
“…High-intensity interval training (HIIT) is a promising, time-saving training program for PwMS that efficiently improves aerobic capacity [21][22][23] and fatigue [21]. Recent intervention studies show that, in contrast to moderate continuous training (MCT), HIIT reduces indicators of inflammatory activity (serum levels of matrix metalloproteinase-2 (MMP-2) [22]) and the neutrophil-to-lymphocyte ratio (NLR) [24], associated with disability status, symptomatology and disease activity. In addition, we and others have shown that physical exercise seems to influence further biological processes, such as the kynurenine (KYN) pathway, which play a crucial role in the pathogenesis and progress of MS [22].…”
Section: Introductionmentioning
confidence: 99%